The kinematic analysis of basketball three point shoot after high intensity program - Tsai, C.-Y.; Ho, W.-H.; Li, Y.-K.; Huang, C.-L. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to analyze kinetic and kinematic characteristics of three points shooting by high speed camera. Basketball players have to finish the high intensity program which was designed from simulative basketball games. The high intensity testing program includes dribbling, sprint, slide, jump shooting and three points shooting. The results of the experiments indicated that elbow, wrist, hip and ankle joints angle velocities would decrease, except the knee joint, after the high intensity program. The knee angle of take-off would also increase. It indicated that the upper limb joints angular velocity would decrease and players had to increase knee joint angular velocity to maintain original power. The time from take-off to ball release also decreased which means that there was a change in the coordinates in knee joint and elbow joint. After high intensity program the elbow and knee joints extension were closed to produce more power for the shot.